DRAFT GUIDELINE FOR MANUSCRIPT SUBMISSION - Ni Made Suaniti (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2018)
DRAFT GUIDELINE FOR MANUSCRIPT SUBMISSION